Micro electro discharge machining for nonconductive ceramic materials - Ali, Mohammad Yeakub (2017)
In micro-electro discharge machining (micro-EDM) of nonconductive ceramics, material is removed mainly by spalling due to the dominance of alternating thermal load. The established micro-EDM models established for single spark erosion are not applicable for nonconductive ceramics because of random spalling. Moreover, it is difficult to create single spark on a nonconductive ceramic workpiece when the spark is initiated by the assisting electrode. In this paper, theoretical model of material removal rate (MRR) as the function of capacitance and voltage is developed for micro-EDM of nonconductive zirconium oxide (ZrO2). It is shown that the charging and discharging duration depend on the capacitance and resistances of the circuit. The number of sparks per unit time is estimated from the single spark duration s derived from heat transfer fundamentals. The model showed that both the capacitance and voltage are significant process parameters where any increase of capacitance and voltage increases the MRR. However, capacitance was found to be the dominating parameter over voltage. As in case of higher capacitances, the creation of a conductive carbonic layer on the machined surface was not stable; the effective window of machining 101 - 103 pF capacitance and 80 - 100 V gap voltage or 10 - 470 pF capacitance and 80 - 110 V gap voltage. This fact was confirmed EDX analysis where the presence of high carbon content was evident. Conversely, the spark was found to be inconsistent using parameters beyond these ranges and consequently insignificant MRR. Nevertheless, the effective number of sparks per second were close to the predicted numbers when machining conductive copper material. In addition, higher percentage of ineffective pulses was observed during the machining which eventually reduced the MRR. In case of validation, average deviations between the predicted and experimental values were found to be around 10%. Finally, micro-channels were machined on nonconductive ZrO2 as an application of the model.